2017
DOI: 10.1159/000480221
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Prescription in the Prevention of Intradialytic Hypotension: New Insights into an Old Concept

Abstract: Background: Sodium prescription in patients with intradialytic hypotension remains a challenge for the attending nephrologist, as it increases dialysate conductivity in hypotension-prone patients, thereby adding to dietary sodium levels. Methods: New sodium prescription strategies are now available, including the use of a mathematical model to compute the sodium mass to be removed during dialysis as a physiological controller. Results: This review describes the sodium load of patients with end-stage renal dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The system that uses sodium sensor in hemofiltration with endogenous reinfusion is called hemodiafiltration Aequilibrium (HFR-Aeq). 47 In a randomized crossover multinational study, Locatelli et al reported that significantly less symptomatic IDH was seen in HFR-Aeq, and the effect was significantly greater in unstable patients. No evidence of sodium or water overload was detected with the intervention.…”
Section: Sodium Profiling As a Part Of Dialysis Modalities And Biofeedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…The system that uses sodium sensor in hemofiltration with endogenous reinfusion is called hemodiafiltration Aequilibrium (HFR-Aeq). 47 In a randomized crossover multinational study, Locatelli et al reported that significantly less symptomatic IDH was seen in HFR-Aeq, and the effect was significantly greater in unstable patients. No evidence of sodium or water overload was detected with the intervention.…”
Section: Sodium Profiling As a Part Of Dialysis Modalities And Biofeedbackmentioning
confidence: 99%
“…These models use real‐time data from patients and are being used to reach end‐dialysis sodium, weight, and blood volume targets. Such biofeedback systems enable to achieve sodium balance neutral sodium profile and UF profile automatically 47–49 . Currently, there are various commercial dialysis systems that calculate dialysate and UF profiles with algorithms based on the prescribed decrease in body weight and sodium mass 50 …”
Section: Sodium Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…Good agreement is reported between natremia measured by a laboratory device (Na Lab ) and plasma-water conductivity (Γ P ) with a correlation coefficient of about 0.9 (range 0.77-0.97) depending on the method of measurement for plasma sodium and plasma-water conductivity. 4,5,[8][9][10][11][12][13][14][15] The Na Lab /Γ P ratio is very close to 10 (mmol/L)/(mS/cm) in the usual range of values (Table 1), so the Γ P value (mS/cm) can be converted to an online natremia value (mmol/L) before being displayed on the screen of some hemodialysis machines. 16,17 Although the concentration of cations other than sodium (mainly potassium) can be neglected relative to sodium concentration (5% vs. 95%), the variation in their plasma concentration during a dialysis session cannot be neglected relative to the variation of natremia.…”
Section: Conductivity and Sodium In Dialysis Fluidmentioning
confidence: 99%
“…As sodium is the predominant ion in both plasma and dialysate, then conductivity measurements can be used to estimate sodium activity. Thus, by measuring conductivity in both plasma an dialysate, then dialysate sodium can be adjusted accordingly to achieve isonatric dialysis 28 . Preliminary studies have reported that this automatic adaptive technology reduced the number of hypotensive dialysis sessions complicated by IDH 29 .…”
Section: Dialysate Sodiummentioning
confidence: 99%